The Influence of Application of The Discovery Learning Model and Learning Styles on Science Learning Outcomes in Primary School Students - Hairul Anam; Muh Fahrurrozi; Khirjan Nahdi (Sumber Belajar Sejahtera, 2023)
The aim of this research is to determine the effect of implementing the discovery learning model and learning styles on the learning outcomes of fifth grade elementary school students. The research method uses quantitative experimental methods. The research results show that student learning outcomes using the discovery learning learning model and learning styles with a Mean Square number of 429.577 and a significance value of 0.001<0.05 or (A) less than 0.05 means there is a significant influence, which means H1 is accepted. Learning style has a significant influence with a Mean Square of 414,502.817 and a significance value of 0.01, which is smaller than 0.05, meaning it is significant. On the other hand, if we look at the interaction between the model and student learning styles, they can be correlated so that there is an interaction effect using discovery learning and learning styles on student learning outcomes with a Mean Square value of 301.517 with a significance value of 001, which is smaller than 0.05